KOMUNIKASI KELUARGA: REPRESENTASINYA DALAM FILM NANTI KITA CERITA TENTANG HARI INI - Faza, Naufan Haidar; Soedarsono, Dewi K. (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
One of the films released in 2020 is "Nanti Kita Cerita Tentang Hari ini". This fictional film, directed by Angga Dwimas Sasongko, tells the story of a family whose secrets and deep trauma are buried. The family consists of a father and mother named Narendra and Ajeng with three children named Angkasa, Aurora, and Awan. Family communication is one way for the process of communication between families to occur. Therefore, family communication in this film is very important because the main focus of the film is the family in this film itself. This study uses qualitative method with critical paradigm using John Fiske's semiotic analysis technique, where the researcher selects five scenes to study based on the three levels of John Fiske's semiotics, namely reality, representation, and ideology levels. The results indicate that family communication in this film is problematic. From these three levels, it can be seen that this pattern of family communication is one of the reasons why conflicts in the film occur. With the father being authoritarian and controlling, conflicts in the family are evident, especially conflicts related to his children. This indicates that the family communication carried out by this family is not carried out properly.